Temperature Calibrator with Thermocouple Based Microcontroller - Aninda Zakia Febriyanti; Priyambada Cahya Nugraha; Syaifudin Syaifudin (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2020)
Calibration is very important to know the temperature uniformity inside the tool. One of them is at the temperature sterilizer, dry heating sterilizer which is sterilizing the device using a high heat oven. The purpose of this study is to develop a temperature Calibrator tool as a refinement of previously made tools by measuring temperatures more than one point in order to achieve a calibration process that complies with the standard. The working method of a temperature calibration device is that the sensor will detect the temperature which then enters the IC ATMEGA 328 that has been given the program and processed in such a way that the output will be displayed on the LCD 4x20 character in the form of temperature measurement of the device. Based on the results of comparative data between the module and the comparison tool